2019
DOI: 10.3390/nu11102485
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Under-Five Stunting Trend in 14 Low- and Middle-Income Countries since the Turn of the Millennium: A Multilevel Pooled Analysis of 50 Demographic and Health Surveys

Abstract: Background: Understanding the drivers contributing to the decreasing trend in stunting is paramount to meeting the World Health Assembly's global target of 40% stunting reduction by 2025. Methods: We pooled data from 50 Demographic and Health Surveys since 2000 in 14 countries to examine the relationships between the stunting trend and potential factors at distal, intermediate, and proximal levels. A multilevel pooled trend analysis was used to estimate the association between the change in potential drivers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
1
29
0
3
Order By: Relevance
“…After matching 30% of the infants of the DHS are stunted (under -200 which stands for -2Z) of infants not fed with FICs are stunted. This rate is slightly lower than the estimates of Argaw et al but can be explained by the large weight of India in their study [40] but very similar to the one estimated by De Onis [41]. In the FICs group this percentage is around 28%.…”
Section: Figure 4:cumulative Distribution On Heigh-for-age Z-score Onsupporting
confidence: 53%
“…After matching 30% of the infants of the DHS are stunted (under -200 which stands for -2Z) of infants not fed with FICs are stunted. This rate is slightly lower than the estimates of Argaw et al but can be explained by the large weight of India in their study [40] but very similar to the one estimated by De Onis [41]. In the FICs group this percentage is around 28%.…”
Section: Figure 4:cumulative Distribution On Heigh-for-age Z-score Onsupporting
confidence: 53%
“…Globally, inequity, and deprivation are key drivers of child stunting (Argaw et al, 2019) with research from South Asia finding low levels of maternal education and household poverty to be key drivers of child stunting (Rama, Beteille, Li, Matra, & Newman, 2015). In East…”
Section: Poverty and Inequitymentioning
confidence: 99%
“…Various studies across many years have shown that there are many factors associated with the depression of linear growth, including infection, poor diet quality, low socioeconomic status, low birthweight, hypoxia, environmental pollution, deprivation, psychosocial stress, social and economic status, poverty, and structural violence in some countries (Ulijaszek 2006) - Figure 1 illustrates this, incorporating also epigenetics (Ulijaszek in press). A recently published study (Argaw et al 2019) has examined the relationships between change in growth stunting and distal, intermediate, and proximal level factors using multilevel pooled trend analysis of pooled data from 50 Demographic and Health Surveys since 2000 in fourteen countries (Bangladesh, Cambodia, Ethiopia, Haiti, Kenya, Malawi, Mali, Nepal, Nigeria, Rwanda, Tanzania, Uganda, Zambia, and Zimbabwe). These authors found that at a distal level, a decrease in the Gini coefficient, an improvement in women's decision-making, and an increase in urbanization were each significantly associated with a lower probability of within-country stunting.…”
mentioning
confidence: 99%
“…The gini coefficient and urbanisation represent country-level political economic factors, socioeconomic status, social mobility and poverty, while women's decision making reflects cultural and political economic factors. The intermediate-level factors identified by Argaw et al (2019) map onto exposure to infectious disease, while the proximate factors of birthweight and breastfeeding map onto epigenetics, nutrition, and exposure to infection, respectively. The Argaw et al (2019) analysis allows priorities to be set for intervention for reduction in rates of stunting in low and middle income countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation